KEPATUHAN SISWA TERHADAP DISIPLIN DAN UPAYA GURU BK DALAM MENINGKATKANNYA MELALUI LAYANAN INFORMASI - Febrina . Sanderi; marjohan .; Indah . Sukmawati (Universitas Negeri Padang, 2013)
Discipline is the process of learning and the creation of a compliance with the rules that have been established or created in schools to prevent violations. Various problems encountered with regard to compliance of students to comply with school rules and regulations, therefore it is necessary efforts BK teachers in improving student discipline through the information service. This study aims to describe students' opinions about the discipline and the efforts of teachers to increase BK. The study was descriptive, the sample is in the eighth grade students of SMP Negeri 26 Padang. Keywords: Compliance, Discipline, Teacher Effort BK, Information Services